Subsurface metals fatigue cracking without and with crack tip (Fracture and Structural Integrity, 2013)
Very-High-Cycle-Fatigue regime for metals was considered and mechanisms of the subsurface crack origination were introduced. In many metals first step of crack origination takes place with specific area formation because of material pressing and rotation that directed to transition in any volume to material ultrahigh-plasticity with nano-structure appearing. Then by the border of the nano-structure takes place volume rotation and fracture surface creates with spherical particles which usually named Fine-Granular-Area. In another case there takes place First-Smooth-Facet occurring in area of origin due to whirls appearing by the one of the slip systems under discussed the same stress-state conditions. Around Fine-Granular-Area or First- Smooth-Facet there plastic zone appeared and, then, subsurface cracking develops by the same manner as for through cracks. In was discussed quantum-mechanical nature of fatigue crack growth in accordance with Yang’s modulus quantization for low level of deformations. New simply equation was considered for describing subsurface cracking in metals out of Fine-Granular-Area or Fist-Smooth-Facet.
Keywords: Quantum-mechanical